(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Anemia is considered a public health problem that affects a third of the population and contributes to increased morbidity and mortality, decreased work productivity, and impaired neurological development. Anemia is known as a condition in which either the number of red blood cells or their oxygen-carrying capacity is lower than normal and insufficient to meet body physiological needs. After bariatric surgery, iron deficiency develops as a consequence of the alterations in the gastrointestinal anatomical architecture and the associated changes in the physiology of the gastrointestinal tract. Several factors involved in the development of iron deficiency after bariatric surgery such as reduced iron intake, reduced secretion of hydrochloric acid and a reduction in the surface area for absorption. Unlike certain heavy metals such as iron or lead, which receive a great deal of attention during formal medical education, copper’s role in the human body often goes neglected except during brief discussions of Wilson’s disease. Bariatric surgery has arisen as a tremendously helpful modality for improving weight loss and other comorbidities, such as type 2 diabetes. The number of bariatric and metabolic surgeries has been on the rise, up to 216,000 procedures in 2016 (a marked 10% increase from 2015). A large number of patients undergoing bariatric surgery are deficient in copper, and Roux-en-Y gastric bypass can further aggravate it. Delays in diagnosis and treatment of copper deficiency can leave patients with residual neurological disability. This has led to recommendation from the British Obesity and Metabolic Surgery Society that copper levels should be monitored annually after gastric bypass.